2015
DOI: 10.1007/s11442-015-1245-0
|View full text |Cite
|
Sign up to set email alerts
|

Slope spectrum critical area and its spatial variation in the Loess Plateau of China

Abstract: Slope spectrum has been proved to be a significant methodology in revealing geomorphological features in the study of Chinese loess terrain. The determination of critical areas in deriving slope spectra is an indispensable task. Along with the increase in the size of the study area, the derived spectra are becoming more and more alike, such that their differences can be ignored in favor of a standard. Subsequently, the test size is defined as the Slope Spectrum Critical Area (SSCA). SSCA is not only the founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…As one of the most typical areas of loess deposit in the world, the Loess Plateau of China that features unique loess landform and severe soil erosion issue has attracted widespread attention for scholars in the fields of geomorphology, geology, hydrology, ecology, and soil and water conservation (Shi and Shao 2000;Hessel and van Asch 2003;Tang et al 2008; Li and Tang 2011;Wang et al 2013;Tang et al 2015;Xiong et al 2016). Gullies, as vessels of material and energy transportation during earth surface processes (Perron et al 2009;Willett et al 2014;Shruthi et al 2015;Xiong et al 2017), are the most active geomorphic units and widely distributed in the Loess Plateau and other regions (Korzeniowska et al 2018;Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most typical areas of loess deposit in the world, the Loess Plateau of China that features unique loess landform and severe soil erosion issue has attracted widespread attention for scholars in the fields of geomorphology, geology, hydrology, ecology, and soil and water conservation (Shi and Shao 2000;Hessel and van Asch 2003;Tang et al 2008; Li and Tang 2011;Wang et al 2013;Tang et al 2015;Xiong et al 2016). Gullies, as vessels of material and energy transportation during earth surface processes (Perron et al 2009;Willett et al 2014;Shruthi et al 2015;Xiong et al 2017), are the most active geomorphic units and widely distributed in the Loess Plateau and other regions (Korzeniowska et al 2018;Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This also indicated the variation in erosion pattern during the extreme rainstorm. Forest, grassland and cropland accounted for 62·2%, 27·1% and 6·9% of the area of the catchment, respectively, and the remaining 3·8% of the area resulted in a gully density of about 2·1 km −2 , which is much lower than the average gully density (approximately 8·3 km −2 ) in the hilly loess areas of northern Shaanxi Province (Tang et al ., ). Despite their relatively low density, these gullies were responsible for a large proportion of the erosion in the catchment.…”
Section: Discussionmentioning
confidence: 97%
“…The loess landform types in the three areas studied represent a loess tableland, loess ridge, and loess hill. The selected catchments are representative of loess landform types, as many previous studies can be found (Cao et al, ; Tang, Song, Li, Zhang, & Xiong, ; Xiong, Tang, Li, Yuan, & Lu, ; Zhou et al, ). The morphological features are significant when selecting sample areas, and areas with various mixed terrain features or transitional zones are largely avoided.…”
Section: Methodsmentioning
confidence: 99%